Analisis Strategi Komunikasi Persuasif Host Live Streaming Marketing Brand Skincare Lokal @somethincofficial DI Tiktok - Liwa, Santika Negeri Ratu; Mardiana, Lisa (Universitas Garut, 2025)
AbstractThere's a competition between skincare brands that race to market their products so businessmen are charged with adapting to evolving technology. Trade through social media has become an important aspect of smooth economic activity so that it can run as expected. The use of social media in marketing has a positive impact on marketers like increasing online sales. Social media Tiktok supports the existence of online marketing phenomenon that presents TikTok live streaming and TikTok Shop interconnected features. Live streaming has become a popular phenomenon with a lot of fans among hosts and also audiences. In live streaming marketing, the host can demonstrate the product by delivering product information in real time. The research aims to find out the persuasive communication strategies of TikTok @somethincofficial's live streaming marketing hosts to attract the attention of audiences and purchase decisions. This research uses qualitative methods with the type of content analysis research. Techniques of data collection through observation and documentation. This research data is obtained from a screenshot of TikTok account @somethincofficial on event double date (7.7). The study uses references to DeFleur and Ball Rokeach's theory of persuasive communication strategies and Howell's Theory of Persuasive Communication Techniques. The @somethincofficial account uses psychodynamic, sociocultural, the meaning construction, and the five persuasive communication techniques of transfer, putting it up to you, bandwagon, say it with flowers, reassurance. In addition, the researchers found non-verbal communication performed by some live streaming @somethincofficial hosts with smiling gestures, pointing, pushing the thumb, whistling, hand swinging, and eye or eye contact movements.Keywords: Live streaming, marketing, persuasive communication, TikTok, persuasive communication strategy AbstrakAdanya persaingan antar brand skincare yang berlomba-lomba dalam memasarkan produknya sehingga pelaku bisnis dituntut untuk bisa beradaptasi dengan teknologi yg semakin berkembang. Perdagangan melalui sosial media menjadi aspek penting dalam kelancaran aktivitas ekonomi sehingga dapat berjalan sesuai harapan. Pemanfaatan sosial media dalam pemasaran memiliki dampak yang positif bagi marketer seperti meningkatkan penjualan yang dilakukan secara daring. Sosial media Tiktok mendukung adanya fenomena pemasaran online yang menghadirkan fitur TikTok live streaming dan TikTok Shop yang saling berkesinambungan. Live streaming menjadi fenomena yang populer dengan banyaknya peminat antara host dan juga audiens. Dalam live streaming marketing host dapat mendemonstrasikan produk dengan menyampaikan informasi produk secara real-time. Penelitian ini bertujuan untuk mengetahui strategi komunikasi persuasif host live streaming marketing akun Tiktok @somethincofficial untuk menarik perhatian audiens dan keputusan pembelian. Penelitian ini menggunakan metode kualitatif dengan jenis penelitian analisis konten (conten analysis). Teknik pengumpulan data melalui observasi dan dokumentasi. Data penelitian ini diperoleh dari rekaman layar akun TikTok @somethincofficial pada event double date (7.7). Penelitian ini menggunakan rujukan teori strategi komunikasi persuasif DeFleur dan Ball Rokeach dan teori teknik komunikasi persuasif Howell. Akun @somethincofficial menggunakan strategi psikodinamika, sosiokultural, the meaning construction, dan kelima teknik komunikasi persuasif yaitu transfer, putting it up to you, bandwagon, say it with flowers, reassurance. Selain itu, peneliti menemukan komunikasi non verbal yang dilakukan oleh beberapa host live streaming @somethincofficial dengan gestur senyum, menunjuk, mengacungkan jempol, melambai, mengayunkan tangan, dan gerakan mata atau eye contact.Kata-kata Kunci: Live streaming, marketing, komunikasi persuasif, TikTok, strategi komunikasi persuasif